Design, 3D printing and testing of architectured materials with bistable interlocks. (February 2017) - Mirkhalaf, Mohammad; Barthelat, Francois
Abstract: Mechanisms associated with geometric interlocking are critical in engineering materials such as adhesives, metals or composites, and also in natural materials such as diatoms or mollusk shells. In this work we developed a new type of sutured material based on jigsaw-like morphologies which can be programmed to geometrically lock into two distinct stable positions. Using 3D printing and design exploration, we show that the mechanical response of these bistable materials can be tailored by fine tuning of the architecture of the tabs. The system can be cycled between the two equilibrium positions without apparent damage accumulation. We also show that the second equilibrium position can be made more stable than the first, effectively providing a geometric hardening mechanism to delay localization and spread nonlinear deformations over large volumes of material. The resulting materials are up to 10 times tougher than the polymer they are made of and they offer attractive properties such as large and reversible deformations, damage tolerance and re-manufacturability, offering promising perspectives in the development of new architectured materials. Graphical abstract: